Functional Potential of Multilingual Text in Urban Space: a Linguistic-Semiotic Perspective - O. A. Alimuradov; M. A. Gorbunova (Научный диалог, 2023)
This article analyzes the functional potential of multilingual texts within urban spaces from a linguistic-semiotic perspective. The study uses a sample of 1590 multilingual texts, consisting of photographs of graffiti objects found in four cities in Southern Russia: Nalchik, the Novorossiysk agglomeration (Novorossiysk and Myskhako), Pyatigorsk, and Rostov-on-Don. The methods used include continuous sampling of multilingual texts, content analysis of their verbal elements, semiotic analysis of their graphic elements, comparative and contrastive methods, and quantitative data processing techniques. The phenomenon of graffiti is analyzed from linguistic and linguo-semiotic perspectives, with a distinction made between graffiti and street art. The authors describe the ontology of graffiti in the urban environment through a series of important dichotomies: visibility / invisibility, performance / risk / art, and sanction/unsanction. The functions of graffiti are also examined in detail, including their integrative-identifying function, self-presentation function, protest function, subversive function, and advertising / propaganda function. The study concludes that multilingual texts, represented in the form of graffiti within urban spaces, have significant functional potential.